Factorise each of the following:

(i) $8 a^{3}+b^{3}+12 a^{2} b+6 a b^{2}$

(ii) $8 a^{3}-b^{3}-12 a^{2} b+6 a b^{2}$

(iii) $27-125 a^{3}-135 a+225 a^{2}$

(iv) $64 a^{3}-27 b^{3}-144 a^{2} b+108 a b^{2}$

(v) $27 p^{3}-\frac{1}{216}-\frac{9}{2} p^{2}+\frac{1}{4} p$
Solution:

It is known that,

$(a+b)^{3}=a^{3}+b^{3}+3 a^{2} b+3 a b^{2}$

and $(a-b)^{3}=a^{3}-b^{3}-3 a^{2} b+3 a b^{2}$

(i) $8 a^{3}+b^{3}+12 a^{2} b+6 a b^{2}$

$=(2 a)^{3}+(b)^{3}+3(2 a)^{2} b+3(2 a)(b)^{2}$

$=(2 a+b)^{3}$

$=(2 a+b)(2 a+b)(2 a+b)$

(ii) $8 a^{3}-b^{3}-12 a^{2} b+6 a b^{2}$

$=(2 a)^{3}-(b)^{3}-3(2 a)^{2} b+3(2 a)(b)^{2}$

$=(2 a-b)^{3}$

$=(2 a-b)(2 a-b)(2 a-b)$

(iii) $27-125 a^{3}-135 a+225 a^{2}$

$=(3)^{3}-(5 a)^{3}-3(3)^{2}(5 a)+3(3)(5 a)^{2}$

$=(3-5 a)^{3}$

$=(3-5 a)(3-5 a)(3-5 a)$

(iv) $64 a^{3}-27 b^{3}-144 a^{2} b+108 a b^{2}$

$=(4 a)^{3}-(3 b)^{3}-3(4 a)^{2}(3 b)+3(4 a)(3 b)^{2}$

$=(4 a-3 b)^{3}$

$=(4 a-3 b)(4 a-3 b)(4 a-3 b)$

(v) $27 p^{3}-\frac{1}{216}-\frac{9}{2} p^{2}+\frac{1}{4} p$

$=(3 p)^{3}-\left(\frac{1}{6}\right)^{3}-3(3 p)^{2}\left(\frac{1}{6}\right)+3(3 p)\left(\frac{1}{6}\right)^{2}$

$=\left(3 p-\frac{1}{6}\right)^{3}$

$=\left(3 p-\frac{1}{6}\right)\left(3 p-\frac{1}{6}\right)\left(3 p-\frac{1}{6}\right)$
Editor